Characterization and Functional Analysis of Voltage‐Dependent Anion Channel 1 (VDAC1) from Orange‐Spotted Grouper (Epinephelus coioides). Issue 7 (30th May 2014) - Shi, Yan; Zhao, Zhe; Hong, Xiaoyou; Chen, Kunci; Zhu, Xinping
ABSTRACT The voltage‐dependent anion channel (VDAC) is a highly conserved integral protein of mitochondria in different eukaryotic species. It forms a selective channel in the mitochondrial outer membrane that serves as the controlled pathway for small metabolites and ions. In this study, a VDAC gene, EcVDAC1, was isolated from orange‐spotted grouper (Epinephelus coioides). The EcVDAC1 exhibits ubiquitous expression in various tissues of orange‐spotted grouper and is upregulated in liver, gill, and spleen after stimulation with lipopolysaccharides (LPS). Subcellular localization analysis shows that the EcVDAC1 protein colocalized with the mitochondria. A caspase‐3 assay demonstrates that overexpression of the EcVDAC1 induced apoptotic cell death in fathead minnow cells. The data presented in this study provide new information regarding the relationship between LPS and the EcVDAC1 gene, suggesting that the fish VDAC1 gene may play an important role in antibacterial immune response.